1993
DOI: 10.5636/jgg.45.775
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Interpretation of Geomagnetic Induction Response Across the Thrust Zones of the Himalaya along the Ganga-Yamuna Valley.

Abstract: Geomagnetic variations, recorded through a two-phase magnetovariational study carried out along the Ganga-Yamuna valley of the Garhwal Himalaya, northwest India, are reduced to a set of induction arrows spanning a period range of 12-128 minutes. The spatial behaviour of induction response indicates that the Main Frontal Thrust is a major electrical discontinuity with enhanced conductivity to the south, beneath the Indo-Gangetic plains. Simple two-dimensional (2-D) geoelectrical models with geophysical constrai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
1

Year Published

1997
1997
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 28 publications
0
12
1
Order By: Relevance
“…From the Geomagnetic depth sounding (GDS) studies, Reddy and Arora (1993) have reported a high conductivity layer embedded in the crust at depths varying from 10-15 km below the Himalayan collision region. They have noted that the real induction vectors have maximum length near the MFT and become smaller towards the MBT on the NE and the Indo-Gangetic plains on the SW, indicating a large conductance for this conductive layer below MFT.…”
Section: Geology and Tectonic Setting Of Siwaliksmentioning
confidence: 99%
“…From the Geomagnetic depth sounding (GDS) studies, Reddy and Arora (1993) have reported a high conductivity layer embedded in the crust at depths varying from 10-15 km below the Himalayan collision region. They have noted that the real induction vectors have maximum length near the MFT and become smaller towards the MBT on the NE and the Indo-Gangetic plains on the SW, indicating a large conductance for this conductive layer below MFT.…”
Section: Geology and Tectonic Setting Of Siwaliksmentioning
confidence: 99%
“…The northward directed arrows at the northern sites of the UP-West Nepal profile suggests the presence of a conducting zone beneath the higher Himalaya (Pandey and Arora, 1997). The THC and some other anomalies whose induction response were found to be compatible with 2-D structure, have already been modelled using 2-D formulation earlier (Arora, 1990;Reddy and Arora, 1993 sufficient to explain 3-D conductivity distribution in the region. As the 3-D modelling is unwieldy, thin-sheet approximation (3-D) of variable conductance is considered suitable to provide unified picture of near surface 3-D conductivity distribution.…”
Section: Introductionmentioning
confidence: 98%
“…3 and 4 indicates that the region west of ISC has more complex electrical conductivity distribution than that of the east. On the west, prominent induction anomalies include two high conducting zones parallel to the strike of the Himalaya, which correspond to the two hump-shaped anomalies in 2-D model developed by Reddy and Arora (1993). These two conducting zones together with a localized and narrow conducting zone coincident with the GLHSB (Reddy and Arora, 1992a, b) collectively seen as furrowed conducting zones running approximately parallel to the MFT and MCT (Fig.…”
Section: Tectonicmentioning
confidence: 99%
See 2 more Smart Citations